The Increased Likelihood in the 21st Century for a Tropical Cyclone to Rapidly Intensify When Crossing a Warm Ocean Feature—A Simple Model’s Prediction - Leo Oey (Atmosphere, 2021)
A warm ocean feature (WOF) is a blob of the ocean’s surface where the sea-surface temperature (SST) is anomalously warmer than its adjacent ambient SST. Examples are warm coastal seas in summer, western boundary currents, and warm eddies. Several studies have suggested that a WOF may cause a crossing tropical cyclone (TC) to undergo rapid intensification (RI). However, testing the “WOF-induced RI” hypothesis is difficult due to many other contributing factors that can cause RI. The author develops a simple analytical model with ocean feedback to estimate TC rapid intensity change across a WOF. It shows that WOF-induced RI is unlikely in the present climate when the ambient SST is ≲29.5 °C and the WOF anomaly is ≲+1 °C. This conclusion agrees well with the result of a recent numerical ensemble experiment. However, the simple model also indicates that RI is very sensitive to the WOF anomaly, much more so than the ambient SST. Thus, as coastal seas and western boundary currents are warming more rapidly than the adjacent open oceans, the model suggests a potentially increased likelihood in the 21st century of WOF-induced RIs across coastal seas and western boundary currents. Particularly vulnerable are China’s and Japan’s coasts, where WOF-induced RI events may become more common.